Selected Factors Against Functional Performance in Patients in the Early Period After Stroke. Issue 4 (October 2017) - Przysada, Grzegorz; Leszczak, Justyna; Czenczek-Lewandowska, Ewelina; Podgórska-Bednarz, Justyna; Wyszyn´ska, Justyna; Baran, Joanna; Weres, Aneta; Druz·bicki, Mariusz
Abstract : The main objective of the study was to evaluate the impact of selected clinical factors on functional performance in 693 patients in the early period after stroke. The level of functional performance of each patient was evaluated twice (before and after 4 weeks of rehabilitation) using the short version of the Barthel Index. A comprehensive 4-week rehabilitation program significantly improved the functional performance of stroke survivors ( P = .0001). There was no significant relationship between functional improvement and age ( P = .3800), sex ( P = .4085), type of stroke ( P = .7498), and side of paresis ( P = .1573).